A revival of budget deficit and economic growth - Elisha Mavodyo (Economics and Econometrics Research Institute (EERI), 2020)
South Africa has experienced high budget deficits accompanied by sluggish economic growth over the years. Fears mount that such a trend may worsen due to the advent of the Covid-19. Yet, the effect of budget deficit on economic growth remains one of the widely debated topics in economics. This article gives empirical evidence on the budget deficit-economic growth nexus and the deficit spending channels that are growth stimulating in South Africa over the period 1980 to 2018. Relying on the Dynamic Ordinary Least Squares (DOLS), results show that budget deficit is growth promoting and that budget deficit is growth stimulating if it is channelled towards export-oriented industrialisation of ores and metals
Keywords: C14; C25; C61; 330; DOLS; endogeneity; budget deficit; economic growth; export-oriented industrialisation